KEDUDUKAN DAN TANGGUNG JAWAB KORPORASI MULTINATIONAL (MNC/TNC) DALAM BIDANG PERTAMBANGAN TERKAIT KEJAHATAN PENCEMARAN LINGKUNGAN - Sumartini, Siti (Universitas Wiralodra, 2016)
In Globalization era has emerged non state actors, i.e Multi National Corporations (MNCs) come to the world as a new actor beside of the other actors. MNCs have unique activity that sometimes inimical the rights of the people and environment. This potential inimical should be well defined- arranged by state. It means that MNCs should be an actor or subject of international law. Thus, it is necessary to become MNCs have international legal personality. In order to, the rights and obligations of MNCs can be accommodated properly. Enforcing Environmental law especially mining aspect can be influenced by MNCs performance.